2020
DOI: 10.1074/jbc.ra119.011222
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionarily conserved deubiquitinase UBH1/UCH-L1 augments DAF7/TGF-β signaling, inhibits dauer larva formation, and enhances lung tumorigenesis

Abstract: Modification of the transforming growth factor β (TGF-β) signaling components by (de)ubiquitination is emerging as a key regulatory mechanism that controls cell signaling responses in health and disease. Here, we show that the deubiquitinating enzyme UBH-1 in Caenorhabditis elegans and its human homolog, ubiquitin C-terminal hydrolase-L1 (UCH-L1), stimulate DAF-7/TGF-β signaling, suggesting that this mode of regulation of TGF-β signaling is conserved across animal species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Male TβRII fl/fl and TβRII iΔLEC mice (7-12 weeks old) were subcutaneously implanted with LLCs (2.5 × 10 5 cells) in 100 μl of PBS. Tumor volumes (V) were calculated using the following formula: length × width × width × 0.5 [13]. The tumors were surgically removed and embedded into a frozen section compound (Leica).…”
Section: In Vivo Xenograftsmentioning
confidence: 99%
“…Male TβRII fl/fl and TβRII iΔLEC mice (7-12 weeks old) were subcutaneously implanted with LLCs (2.5 × 10 5 cells) in 100 μl of PBS. Tumor volumes (V) were calculated using the following formula: length × width × width × 0.5 [13]. The tumors were surgically removed and embedded into a frozen section compound (Leica).…”
Section: In Vivo Xenograftsmentioning
confidence: 99%
“…Indeed, analysis of multiple invertebrate species revealed that they harbor a single homologous gene corresponding to GDF11 and MSTN 10 . For instance, in Caenorhabditis elegans, daf-7 was shown to encode a homolog of GDF11 and MSTN, while in fruit flies (Drosophila melanogaster), myoglianin (Myo) was found to exhibit the highest sequence homology to GDF11 and MSTN [10][11][12][13] . An important question that arose from these identifications was whether the divergence of GDF11 and MSTN occurred at the time of the emergence of vertebrates.…”
Section: Evolutionary Analysis Of Gdf11 and Mstnmentioning
confidence: 99%
“…The reason for and functional significance of the divergence of the two mstn genes in fish remains to be clarified. Interestingly, many of the reported functions of the invertebrate MSTN/GDF11 protein are very different from the well-established suppressive role of vertebrate MSTN in the development of multiple tissues, and the broad expression pattern of the ancestral protein more closely resembles the expression pattern of vertebrate GDF11 11,13,[15][16][17][18][19] . These observations imply that MSTN most likely emerged from the ancestral gene to allow more specific control of skeletal muscle growth in vertebrates, although the relatively small amount of information available on the function of invertebrate MSTN/ GDF11 limits further interpretation.…”
Section: Evolutionary Analysis Of Gdf11 and Mstnmentioning
confidence: 99%
See 2 more Smart Citations